The «Prophet of the Biopolitical Diagram». Antonio Negri's Gramsci - Maltese, Pietro (International Gramsci Journal, 2025)
The aim of this paper is to reconstruct Antonio Negri’s path of approach and recovery of Gramsci’s theory. To this end, the trajectory of the philosopher will be taken into consideration from the 1960s up to his writings with Michael Hardt. This study will show the progressive appropriation of some Gramscian categories (hegemony, passive revolution, modern Prince) to understand contemporaneity and organize an antagonistic practice with respect to the existing one.